2016
DOI: 10.1002/ehf2.12096
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to goals of care discussions with hospitalized patients with advanced heart failure: feasibility and performance of a novel questionnaire

Abstract: AimsGood end‐of‐life communication and decision‐making are important to patients with advanced heart failure (HF) and their families, but their needs remain unmet. In this pilot study, we describe the feasibility and performance of a novel questionnaire aimed at identifying barriers and solutions to improve communication and decision‐making about goals of care for hospitalized patients with advanced HF.MethodsWe distributed questionnaires to staff cardiologists, cardiology trainees, and cardiology nurses who p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
(50 reference statements)
2
15
0
Order By: Relevance
“…In this regard, in line with efforts to involve all healthcare professionals in improving end-of-life management across the spectrum of the healthcare pathway, it is essential that nurses be involved in the discussions regarding end-of-life decisions, and they may also be involved in the communication with the patient about end-of-life matters. According to a survey performed by Aleksova among cardiologists, cardiology trainees and cardiology nurses providing care for heart failure patients, nurses were more willing than physicians to initiate and engage in end-of-life discussions with patients [ 25 ]. In this same study, among non-physician clinicians, advanced practice nurses were deemed to be most acceptable to be involved in decision-making relating to goals of care [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, in line with efforts to involve all healthcare professionals in improving end-of-life management across the spectrum of the healthcare pathway, it is essential that nurses be involved in the discussions regarding end-of-life decisions, and they may also be involved in the communication with the patient about end-of-life matters. According to a survey performed by Aleksova among cardiologists, cardiology trainees and cardiology nurses providing care for heart failure patients, nurses were more willing than physicians to initiate and engage in end-of-life discussions with patients [ 25 ]. In this same study, among non-physician clinicians, advanced practice nurses were deemed to be most acceptable to be involved in decision-making relating to goals of care [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a survey performed by Aleksova among cardiologists, cardiology trainees and cardiology nurses providing care for heart failure patients, nurses were more willing than physicians to initiate and engage in end-of-life discussions with patients [ 25 ]. In this same study, among non-physician clinicians, advanced practice nurses were deemed to be most acceptable to be involved in decision-making relating to goals of care [ 25 ]. However, it is important that the physicians do not shirk responsibility by having nurses play a role that the patient traditionally expects the physician to play.…”
Section: Discussionmentioning
confidence: 99%
“…1,6,9 It is well known that comorbidities influence the pathophysiology, management, and prognosis of advanced HF, contributing to increased morbidity and mortality. [1][2][3][4][5][6] Murad et al 10 demonstrated that 60% of elderly patients with HF had at least 3 comorbidities, while only 2.5% of them had none. Renal and liver dysfunction significantly increases mortality associated with HF.…”
mentioning
confidence: 99%
“…[1][2][3] It is estimated that HF affects approximately 38 million adults worldwide, including at least 15 million Europeans. 2,4 In Poland, about 600 000 to 700 000 people suffer from HF.…”
mentioning
confidence: 99%
See 1 more Smart Citation